STUDI PENGGUNAAN LAHAN (LAND USE) DI KECAMATAN SINGKOHOR KABUPATEN ACEH SINGKIL TAHUN 2015 - Chandra Pangihutan Simamora; Afifuddin Dalimunthe; Budi Utomo (Peronema Forestry Science Journal, 2015)
his study aimed to analyze the function of land uses contained in Singkohor Sub District 2015. This research was located in Singkohor Sub District,of Aceh Singkil Regency by using satellite images of landsat 8. The research method was a supervised classification. Analysis of the data for the image interpretation by using monogram of Sumatera and ground check.   The results showed that land cover in the District Singkohor include forests, plantations, open land, settlements, water bodies, bush, and farm. The largest land use at the location of the research is the type of open land area of 5491.57 Ha and forest area of 4046.67 Ha was expected to be on the wane due to the conversion of land use into other uses such as plantations. In addition, 14 species of plants obtained MPTS (Multi Purpose Tree Species) among the sites that have the advantage among others, have been tested and able to adapt to the environment so that these types of MPTS plants are more prospective in rehabilitation activities.Key Word: Land use, interpretation, Landsat imagery, plant of MPTS